Applying Equity Literacy’s Four Abilities to Middle Schools for the Benefit of Students Experiencing Homelessness - Matthew J Moulton (Middle Grades Review, 2020)
In this essay, I use the McKinney-Vento Homeless Education Assistance Improvements Act of 2001 to define homelessness and describe its prevalence in United States public schools. I present readers with statistics about student homelessness and situate Gorski’s equity literacy within the progressive, equity-oriented foundations of the middle school movement and as a means by which stakeholders could begin to address homelessness in their contexts. After presenting the four abilities of equity literate educators, I apply the abilities to the nuances of student homelessness in the middle grades.
Keywords: equity; student homelessness